Ketimpangan Perlindungan Hukum terhadap Dampak Merokok sebagai Kejahatan Sosiologis yang Belum Terkualifikasi Sebagai Tindak Pidana di Indonesia - ST.Mahmud Syaukat; Muhammad Abdul Zalil (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Smoking in public spaces remains a common practice in Indonesia despite its proven harmful effects on others through secondhand smoke exposure. This condition reflects a gap between social reality and legal construction, where harmful behavior is not fully recognized as a criminal offense. This study aims to analyze smoking as a form of sociological harm that has not been adequately classified as a normative crime within the Indonesian legal system. The research employs a normative juridical method combined with a conceptual approach, focusing on legal norms and theoretical perspectives of social harm. The findings indicate that although regulations on health and smoke-free areas exist, their enforcement remains weak and largely administrative in nature. As a result, the protection of passive smokers is not optimal, and the legal system has yet to fully accommodate the broader concept of harm. This study concludes that there is a significant disparity between the empirical impact of smoking and its legal qualification, highlighting the need for a more responsive legal framework.